¿Why to choose an alternative school? (Praxis Educativa, 2021)
This research aims to identify and reflect on the reasons behind the choice of an alternative education centre for the stage of Early Childhood Education in Spain. For this purpose, it is used a biographical-narrative methodology based on a multiple case study made up of 24 families. That way, four major motivational categories are identified: promotion of the integral development of the person, opposition to the traditional school, search for happiness in childhood and trust in the principles pedagogical. Analysed families especially value a comprehensive education beyond its instrumental purpose, they consider public school as the extreme opposite to the principles and values defended from alternative projects. It concludes by pointing out how these motivations, in addition to having a pedagogical sense, respond to a broader strategy to reproduce their identity and lifestyles.